Spanish Constitution of 1978 is outdated - Abad Caja, Julián (Razón y fe, 2018)
The Basque and Galician elections along with the immediate Catalans elections must be read comprehensively. In Galicia the centripetal force for Spain can be noted while in Basque Country and in Catalonia don´t. The integration due to the Title VIII of the Constitution is in leaps and bounds unknown. But also the secessionist projects can disappear due to lack of reality, to not knowing how firm the opposed reasons along the European and the Spanish reasons are, or to highlight the identity issue of a select part above the basic needs of the whole part.